Agroecological Zones, Agricultural Land Regions and Crop Suitability Classification for Kotawaringin Barat Regency, Kalimantan, Indonesia - Bhermana, Andy (2002)
In land use, not all lands can be optimally used for agricultural purposes because each land is influenced by its natural environment that consist of three main elements: land (soil), climate, and crop. The information of these elements is urgently required as a basic consideration in agriculture and area development planning process. The information of natural environment can be organized into a system of agroecological zone (AEZ) that represent homogeneous biophysical environment condition and refers to the division of an area of land into smaller units, which have similar characteristics related to land suitability. The study was conducted in Kotawaringin Barat Regency, Kalimantan, Indonesia and consists of three main part, i.e. developing agroecological zone (AEZ) system, establishing agricultural land regions, and determining land suitability for some existing crops. The expert system called Land Use program was employed to interpret the basic data. The data inputs and results in the form of digitized maps are component of geographic information system (GIS), which facilitates future utilization, updating, improvement, storing, and displaying. On the basis of climatic and land characteristics data at reconnaissance level with scale of 1: 250,000, and considering that Kotawaringin Barat regency has four slope classes and isohyperthermic temperature regime with the existence of udic moisture regime, this regency is divided into four main zones (I, II, III, and IV) and four subzones (IV. l , IY2, IV.3, and IV. 4). As recommended by expert system, zone I and sub-zone IY2, IV.3 and IV.4 should be allocated for forest to protect natural resources and environment in general, zone II can only be utilized for permanent or perennial crops plantation, zone III for agroforestry, and sub-zone IY1 for annual crops farming. On the basis of agroecological zone (AEZ) system, the present land use can then be changed according to agroecological conditions. Comparison of present land use and AEZ leads to general recommendations on how to improve and manage the current land use through extensification, intensification, and conservation.